Heterostructure formation of BiVO4 with different Bi compounds : role of the heterojunction on photocatalytic properties - Lopes, Osmando Ferreira (Universidade Federal de São Carlos, 2016)
Semiconductors employed as photocatalysts that can be activated by visible irradiation have attracted intense scientific interest due to their applications in heterogeneous photocatalysis. BiVO4 is a semiconductor with band gap value of 2.4 eV; however, this material exhibits poor photocatalytic activity mainly due to the rapid recombination of electron/hole pair. An efficient strategy to overcome this challenge is through the formation of type-II heterostructures. Based on this overview, this work aimed at: (i) developing methods to obtain heterostructures composed of BiVO4 and different bismuth compounds (t-BiVO4, Bi2O3 e Bi2O2CO3), (ii) to evaluate the effect of heterojunction formation on photocatalytic properties, and (iii) to study the mechanisms of charge transfer and organic pollutants degradation. Initially, this work investigated the synthesis of BiVO4 by oxidant peroxide method, and it was observed that the main reason for the poor photoactivity of BiVO4 is its inability to reduce O2 to O2 •-. In order to overcome this challenge, we attempted to obtain heterostructures between monoclinic BiVO4 and tetragonal BiVO4 phases (m-BiVO4/t-BiVO4) by oxidant peroxide method. It was verified that m-BiVO4/t-BiVO4 heterostructures exhibited better photocatalytic performance in the degradation of methylene blue (MB) dye than their isolated phases, under visible irradiation. HRTEM images revealed that the heterostructured sample was composed of nanoparticles with average size of 10 nm, the m-BiVO4/t-BiVO4 interface was also evidenced. The mechanisms of charge transfer between the phases and organic pollutant oxidation were proposed in agreement with the obtained results by XPS, mass spectroscopy and TOC analysis. Holes (h+), superoxide anion (O2 -•) and hydroxyl radicals (•OH) were the primary active species responsible for MB photodegradation. The increase of m-BiVO4/t-BiVO4 heterostructure photoactivity occurred due to the formation of a suitable heterojunction, promoting the effective separation of photogenerated charges. However, this method presented difficulties in the control of heterostructure morphology and composition, because it is based on a simultaneous two-phase crystallization process. Therefore, we developed a novel strategy for heterostructure tailoring driven by solubility difference of two semiconductors that possess at least one metal in common. For this, the formation of heterojunctions by BiVO4 growth on Bi2O3 or Bi2O2CO3 self-sacrificial surface was evaluated. For the Bi2O3/BiVO4 heterostructures, the amount of xiv heterojunctions formed between Bi2O3 and BiVO4 was tuned by synthesis process variables (temperature and V concentration) and the particle size of preformed Bi2O3 (i.e. solubility difference). The heterojunctions were evidenced by HRTEM images, where the growth of BiVO4 nanoparticles on Bi2O3 or Bi2O2CO3 surface was observed. Time resolved photoluminescence and XPS results confirmed that the formation of type-II heterostructure led to increase of charge carriers lifetime. The proposed synthesis strategy showed efficiency in obtaining Bi2O3/BiVO4 and Bi2O2CO3/BiVO4 heterostructures with controlled morphology and composition that improved photoactivity when compared to their isolated phases.
Obtenção de heteroestruturas de BiVO4 com diferentes compostos de bi : papel das heterojunções nas propriedades fotocatalíticas
Keywords: Fotocatálise heterogênea; Vanadato de bismuto; Heteroestrutura; Tratamento de água; Radiação visível; Mecanismo de fotodegradação; Heterogeneous photocatalysis; Bismuth vanadate; Heterostructure; Water treatment; Visible radiation; Photodegradation mechanism; CIENCIAS EXATAS E DA TERRA::QUIMICA